2022
DOI: 10.1177/09544089221104073
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the micro-texture and cutting parameters of ball-end milling cutters to achieve milling stability

Abstract: The machining of titanium alloy can lead to serious tool wear, with this resulting in a lack of milling system stability and chatter. This paper looks at the relationship between milling stability and the use of micro-texturing on cutter surfaces, which aims to reduce tool wear. A stability lobe diagram is first drawn that is based on a dynamic model of the milling of titanium alloy by a ball-end milling cutter. This provides the cutting parameters for a stable domain. A micro-texture distribution model is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Cutting parameters can affect the tool workpiece contact relationship and chip removal, ultimately affecting the stability of the milling system and the machining quality of the workpiece. In order to ensure the performance of ball-end milling cutters, with reference to the CNC tool selection guide and the team's previous research results [23,24], the axial cutting depth range is set to [0.3, 0.5 mm], the feed rate range is [0.06, 1 mm/r], and the cutting speed is [120, 160 m/min]. Due to the characteristic of "balanced dispersion, orderliness and comparability" in orthogonal tables, a few representative experimental conditions can be selected within the inspection range to achieve balanced sampling [25].…”
Section: Methodsmentioning
confidence: 99%
“…Cutting parameters can affect the tool workpiece contact relationship and chip removal, ultimately affecting the stability of the milling system and the machining quality of the workpiece. In order to ensure the performance of ball-end milling cutters, with reference to the CNC tool selection guide and the team's previous research results [23,24], the axial cutting depth range is set to [0.3, 0.5 mm], the feed rate range is [0.06, 1 mm/r], and the cutting speed is [120, 160 m/min]. Due to the characteristic of "balanced dispersion, orderliness and comparability" in orthogonal tables, a few representative experimental conditions can be selected within the inspection range to achieve balanced sampling [25].…”
Section: Methodsmentioning
confidence: 99%
“…The range of values for the weights and factors (a, b, c, d, e, and f) is typically between 0 and 1. When a dragonfly individual has neighboring individuals around it, the position is updated using formula (20). When there are no neighboring individuals around the dragonfly individual, it randomly flies around the search space using Levy flight, and the update formula is shown in Equation ( 21):…”
Section: Multi Objective Optimization Based On the Moda Algorithmmentioning
confidence: 99%
“…In surface texture parameters optimization problems involving multiple contradictory performance indices, single-objective optimization often falls short in achieving superior overall performance, as enhancing one aspect may compromise another. Therefore, scholars address this challenge through multi-objective optimization [17][18][19][20]. Shinde [21] et al studied the influence of groove texture parameters (including position, height, width, number and spacing) on bearing performance, and used the gray correlation method to find an optimal set of parameter combinations to achieve maximum loading capacity and minimal friction torque.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that, compared with a pure-coated tool, the addition of micro-texture made the tool performance better, while a micro-pittexturecoated tool was better than a micro-groove-coated tool in terms of cutting force, white layer thickness and friction coefficient. Tong X [12] designed an orthogonal dry-cutting test, established a micro-texture distribution model under different cutting depths, studied the influence of micro-texture parameters on tool milling performance under variable cutting parameters, and optimized the combination of texture parameters according to different evaluation indexes. To explore the role of micro-textured tools with different shapes in the process of cutting titanium alloys, Wang Liang [13] selected several microtextures with different shapes and designed experiments with cutting parameters and micro-texture parameters as changing factors.…”
Section: Introductionmentioning
confidence: 99%